1996
DOI: 10.1149/1.1837109
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transport Through Polyethylene‐Tetrafluoroethylene‐Copolymer‐Based Membrane Containing Sulfonic Acid Group Prepared by RIGP

Abstract: A novel sulfonic acid false(SO3Hfalse) group containing membrane (SH membrane) was prepared by grafting glycidyl methacrylate onto an ethylene‐tetrafluoroethylene copolymer film with subsequent sulfonation. The graft chains introduced on the SH membrane form a flexible brush‐type structure capable of binding water molecules (30% more than Nafion 117 membrane) and transporting protons. Proton conductivity of the SH membrane was evaluated as a function of SO3H group density. The SH membrane with the SO3H g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Radical concentrations following irradiation have an obvious impact on the grafting yields obtainable. Lee et al25 determined radical concentrations in polyethylene (PE), ETFE, and PTFE following a 100‐kGy absorbed dose. They found that the radical concentration in PTFE was two orders of magnitude lower than in PE and ETFE.…”
Section: Resultsmentioning
confidence: 99%
“…Radical concentrations following irradiation have an obvious impact on the grafting yields obtainable. Lee et al25 determined radical concentrations in polyethylene (PE), ETFE, and PTFE following a 100‐kGy absorbed dose. They found that the radical concentration in PTFE was two orders of magnitude lower than in PE and ETFE.…”
Section: Resultsmentioning
confidence: 99%
“…There is an intensive research effort attempting to achieve low-cost nonperfluorinated ionomer membranes to be used in various electrochemical systems. The radiation-grafting technique has been proposed as a valid option to obtain a variety of ion-conducting polymer membranes [5][6][7]. Some of these membranes are already on the market [8].…”
Section: Introductionmentioning
confidence: 99%
“…The ion conductivity of the membrane was comparable to that of Na®on 1 . 14 Poly(vinylidene ¯uoride), PVDF, has been used as matrix polymer in the preparation of polymer membranes for low temperature fuel cells. 15 We have recently reported the preparation and characterisation of proton conducting membranes with PVDF ®lms as matrices.…”
Section: Introductionmentioning
confidence: 99%